MAINTAIN MENTAL HEALTH IN SCHOOL - Annisa, Faida; Muniroh; Robbani, Adhar Rouhul Ni’am; Rosyid, Jalalul; Musila, Branick Imanuel (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Adolescent health is important in determining the quality of the nation. During the age, problems arise that affect mental health, including anxiety, stress, past trauma, and so on. They need to learn how to maintain their mental health as able as carry out their roles in society. In order to prevent teenage mental health issues, education programs about mental health for pupils serve as a type of community service. The community service took place on December, 13th, 2023 in SMK Kerta Cendekia Sidoarjo. The target of this activity was students aged 12-15 years. There was a process of preparing the activity for approximately 4 weeks by starting the permits from related parties. As a form of evaluation, the activity was attended by 40 students and they took part in the activity cooperative and enthusiastically. They were able to describe the criteria of mental health and how to maintain it.